Comparison of the effects of methamphetamine, bupropion and methylphenidate on the self-administration of methamphetamine by rhesus monkeys - Schindler, Charles W. (2011)
The effectiveness of methadone as a treatment for opioid abuse and nicotine preparations as treatments for tobacco smoking has led to an interest in developing a similar strategy for treating psychostimulant abuse. The current study investigated the effects of three such potential therapies on i.v. methamphetamine self-administration (1 - 30 µg/kg/injection) in rhesus monkeys. When given as a pre-session i.m. injection, a high dose of methamphetamine (1.0 mg/kg) decreased i.v. methamphetamine self-administration but did not affect responding for a food reinforcer during the same sessions. However, the dose of i.m. methamphetamine required to reduce i.v. methamphetamine self-administration exceeded the cumulative amount taken during a typical self-administration session, and pretreatment with a low dose of methamphetamine (0.3 mg/kg) actually increased self-administration in some monkeys at the lower self-administration dose. Like pretreatment with methamphetamine, pretreatment with bupropion (3.2 mg/kg) decreased methamphetamine self-administration but did not affect responding for food. Pretreatment with methylphenidate (0.56 mg/kg) did not significantly alter methamphetamine self-administration. These results suggest that some agonist-like agents can decrease methamphetamine self-administration. Although the most robust effects occurred with a high dose of methamphetamine, safety and abuse liability considerations suggest that bupropion should also be considered for further evaluation as a methamphetamine addiction treatment.